Surga Dalam Literatur Al-Quran - Muhammad Zulfikarullah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
This article examines various views both sufi, theologically and philosophically about the meaning of heaven. The three views differ in defining them due to differences in scientific background among the three. After examining many views, the author finally came to the conclusion that the meaning of heaven was not only related to life in the hereafter as a reward for good for those who believe and do good deeds. In the author's view, heaven can also be interpreted as life on earth that is beautiful, safe, comfortable and peaceful as a reflection / reflection of essential heaven on the Day of Judgment. This author's conclusion arises by relating the general nature of God's love in the world (ar-Rahman) and the special nature of God's love in the hereafter (ar-Raheem).